PENERAPAN PENDEKATAN SAINTIFIK MELALUI EKSPERIMEN DI KELAS DAN PENUGASAN GUNA MENINGKATKAN HASIL BELAJAR DAN KEMAMPUAN BERFIKIR KRITIS SISWA - Nunung Nurlaila; Jeffry Handhika (Papua Journal of Physics Education, 2020)
This study aims to determine the effect of the application of scientific approaches through classroom experiments and assignments to improve learning outcomes and critical thinking skills. Critical thinking is a capability needed in the framework of facing the industrial revolution 4.0 because it is closely related to innovation and 21st century skills. The method used in this study is an experimental model with a single pre-post test design completed with qualitative descriptive analysis using N-Gain. The population of this study was the science students of SMAN 6 Madiun. Material is limited to (2) Elasticity and Hooke's Law and (2) Static Fluid. It was concluded that the application of a scientific approach through Experiments in the classroom and Assignments can improve learning outcomes with sig. smaller than 0.05. NGain scores in the low category for learning outcomes (0.26) and critical thinking (0.24).Keywords: Scientific Approach, Experimental Method, Learning Outcomes, Critical Thinking